TIPE1 Inhibits Breast Cancer Proliferation by Downregulating ERK Phosphorylation and Predicts a Favorable Prognosis - Hu, Wei; Feng, Chun-Mei; Liu, Ling-Yun; Li, Na; Tian, Feng; Du, Jian-Xin; Zhao, Yi; Xiang, Xin-Xin; Liu, Kui; Zhao, Pei-Qing (Frontiers in Oncology, 2019)
TIPE1, which acts as a cell death regulator, has emerged as a tumor suppressor in the process of carcinogenesis. However, our recent research demonstrated that it serves as an oncogene in the pathogenesis of cervical cancer, indicating that the role of TIPE1 in carcinogenesis needs to be further evaluated. In this study, we show that TIPE1 is able to inhibit breast cancer cell growth both in vivo and in vitro. Functionally, TIPE1 inhibits cancer cell proliferation preferentially by downregulating ERK phosphorylation. Furthermore, the expression of TIPE1 is decreased in breast cancer tissues compared to matched adjacent tissues, and its expression is positively correlated with patients' lifespan. These data indicate that TIPE1 suppresses breast cancer proliferation by inhibiting the ERK signaling pathway. This study also suggests that TIPE1 could serve as a potential therapeutic target and a diagnostic biomarker for breast cancer.